National Universities Commission Accredited Programmes and the Efficiency of the Programmes in Selected Universities, Nigeria - Abolo, Evuarherhe Veronica (NIU Journal of Humanities; Vol 4 No 4 (2019): KIU Journal of Humanities, Vol. 4 No. 4, December 2019, 2020)
The university education has been given grander focus as it is the major institution for developing skilled manpower for a developing country like Nigeria. In order to fully acquire the desired development, several programmes are offered by the universities. Emphasis are on the universities to yield maximum productivity in output through National Universities Commission (NUC) accreditation exercise. This study therefore sought to examine the efficiency of the accredited programmes in the universities in terms of their studentsâ€™ enrollment (input) and the turn out graduation rate (output). The participants of the study consist Heads of departments and cohort advisers from the faculty of Education in three South West federal universities. The multi stage sampling technique was used from which five departments based on homogeneity across the universities were selected. The records of students enrolment for five sessions 7735 students was used for the analysis Heads of departments and 60 cohort advisers formed the sample for the interview schedule. A researcher designed result checklist was used to collect data of students from the departments while an interview schedule â€˜â€˜Accredited Courses in the Universities and the Efficiency of the Programmes Interviewâ€ was constructed to solicit responses from Heads of Departments and cohort advisers. The research questions were analysed in   frequency and percentages, the hypothesis was tested with chi square and the interview responses through content analysis. The results of the study showed that the dropout rate of students is low while the repeaters rate is high. Also the accredited programmes are adjudged to be efficient as the graduation rate is above the set benchmark of 60%.while   the hypothesis showed that the accredited programmes relate to the efficiency rate of the programmes. Recommendations such as the government having as its policy remedial distance learning for dropout students and the universities developing intensive coaching for repeaters were proffered to ensure quality of programmes. Keywords :  NUC, accredited programmes, efficiency, graduation rate, dropout, repeaters